Investigating the impact of Social-media marketing on brand awareness and growth of small businesses in the UK - Kabulov Murodjon (Academia One, 2024)
This article explores the impact of social media marketing on brand awareness and small business growth in the UK. The main areas of social media are analyzed. The importance of the brand for the enterprise has been studied. Scientific proposals for the development of the enterprise's activities have been made.
Keywords: explores; social; activities; brand